Imaging Cognitive Impairment and Impulse Control Disorders in Parkinson's Disease - Martín-Bastida, Antonio; Delgado-Alvarado, Manuel; Navalpotro-Gómez, Irene; Rodríguez-Oroz, María Cruz (Frontiers in Neurology, 2021)
Dementia and mild forms of cognitive impairment as well as neuropsychiatric symptoms (i. e., impulse control disorders) are frequent and disabling non-motor symptoms of Parkinson's disease (PD). The identification of changes in neuroimaging studies for the early diagnosis and monitoring of the cognitive and neuropsychiatric symptoms associated with Parkinson's disease, as well as their pathophysiological understanding, are critical for the development of an optimal therapeutic approach. In the current literature review, we present an update on the latest structural and functional neuroimaging findings, including high magnetic field resonance and radionuclide imaging, assessing cognitive dysfunction and impulse control disorders in PD.